Rasio AST/ALT pada Laki-Laki Pengkonsumsi Alkohol di Jalan Mendawai Kota Palangka Raya - Dwi Purbayanti; Muhammad Rizwan Nafarin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Aspartate aminotransferase (AST) and Alanine aminotransferase (ALT) are enzymes predominantly found in hepatocytes, the increased activity in the serum shows liver damage. The AST / ALT ratio is used as a marker for alcoholic liver disease. This study aims to determine the effects of long-term alcohol consumption on the risk of alcoholic liver disease. This study was a descriptive study, involving 20 alcoholic drinkers aged 25-45 years, had consumed alcohol> 5 years and consumed alcohol every day. Our results showed a significant increase (p <0.05) in AST and ALT values based on age group, duration of consumption and dose. While the ratio of AST / ALT, a significant increase was found in the age group and period. In alcohol drinkers, the AST value is higher than ALT. The AST / ALT ratio for heavy drinkers is 1.64. Conclusion: Alcohol-consuming subjects in our study, especially heavy drinkers, were suspected of having a risk of alcoholic liver disease because most had an AST / ALT ratio > 1,5.